industri MEASURING THE ROOTS OF PERFORMANCE DETERMINANTS OF CREATIVE SMALL INDUSTRY FINANCIAL ACCESS BASED - Teguh Ariefantoro; Aprih Santoso; Adhi Pradiptya (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
The purpose of this study is to examine the effect of financial access on financial performance with financial literacy as moderating variables in small creative industries in Semarang. The research sample was 103 people who were obtained by purposive sampling technique, namely respondents who took credit for the authority of the Semarang City Government program. Data were analyzed using MRA (Moderated Regression Analysis) analysis. The result of this research is that financial access has an effect on financial performance. Financial literacy are able to moderate the effect of financial access on financial performance in small creative industries in Semarang.